Carolina lunker sauce - Calkins, Tim; Cobb, Matt (London : Kellogg School of Management, 2006)
The case outlines the state of the recreational fishing industry and how Matt and Russ Cobb came to invent a new fishing attractant called Carolina Lunker Sauce. The produce although receiving high praise from fisherman has a high tag. Russ and Matt Cobb, are debating reducing the price of their new product in order to secure an important first order.
Originally published in Calkins, T., & Cobb, M. (2006). Carolina Lunker Sauce. 5-106-001. Evanston, IL: Kellogg School of Management at Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Fishing -- Equipment and supplies; Carolina Lunker Sauce